Abnormal Quantitative Sensory Testing is Associated With Persistent Pain One Year After TKA - Wright, Tony; Moss, Penny; Sloan, K.; Beaver, R.; Pedersen, Jarle; Vehof, Gerard; Borge, Henrik; Maestroni, Luca; Cheong, Philip (Lippincott Williams and Wilkins, 2015)
Background - Up to 15% of patients report at least moderate persistent pain after TKA. Such pain may be associated with the presence of widespread hyperalgesia and neuropathic-type pain. Questions/purposes - We asked if there was a difference among patients who report moderate to severe pain or no pain at least 12 months after TKA regarding (1) pressure pain threshold, (2) thermal (cold/heat) pain and detection thresholds, and (3) self-reported neuropathic pain. Patients and Method - Fifty-three volunteers were recruited from patients reporting no pain or moderate to severe pain, according to the Knee Society Score©. Differences between the moderate-to-severe and no-pain groups regarding pressure pain, heat and cold thresholds, and self-reported neuropathic-type pain were analyzed using independent t-tests. Results - Patients in the moderate-to-severe pain group exhibited reduced pressure pain threshold in the knee with the TKA (p = 0.025) and at the elbow (p = 0.002). This group also showed greater pain sensitivity to cold at the knee (p = 0.008) and elbow (p = 0.010), and increased heat pain sensitivity at the elbow (p = 0.032). Cold and heat detection thresholds were impaired in this group at the elbow (cold, p = 0.034; heat, p = 0.010), although only heat detection was impaired at the knee (p = 0.009). The moderate-to-severe pain group also reported more neuropathic-type pain (p = 0.001). Conclusion - Persistent pain after TKA was associated with widespread pressure, cold hyperalgesia, and greater neuropathic-type pain. Level of Evidence - Level III, prognostic study.